Effects of Physalis angulata Leaf Extract on Female Reproductive Organs Following Busulfan Injection in Rats - Satyaningtijas, Aryani; Ekastuti, Damiana Rita; Tarigan, Ronald; Prasetyaningtyas, Wahono Esthi; Adnyane, I Ketut Mudite; Mohamad, Kusdiantoro; Rahmadhani, Elsi; Sulistyana, Yanti; Mahendra, Arindina (HAYATI Journal of Biosciences, 2026)
Physalis angulata L. (ciplukan) is traditionally used as an herbal remedy with anticancer and antioxidant properties. At the same time, busulfan, a chemotherapy alkylating agent, causes gonadotoxicity and oxidative stress that impair female reproduction. This study aimed to evaluate the effect of P. angulata on reproductive function after busulfan administration in female rats. Twenty-five 6-week-old female rats were randomly divided into: Group I (control), Group II (busulfan only), Group III (P. angulata only), Group IV (busulfan followed by P. angulata after 14 days), and Group V (busulfan and P. angulata administered for 28 days). FSHR and LHR expression in the ovaries and MDA levels in the ovaries and uterus were measured to assess reproductive changes. Busulfan showed no significant effect on FSHR and LHR, whereas P. angulata induced downregulation, suggesting a potential negative feedback mechanism on ovarian receptors. Ovarian MDA showed a decreasing trend with combined treatments, while uterine MDA peaked after busulfan but declined markedly with P. angulata, indicating its role in alleviating oxidative stress. In conclusion, P. angulata may modulate hormonal balance in rat ovaries and decrease oxidative stress in the uterus after busulfan treatment.